The context and its role in determining the reverse significance in the Noble Qur’an in light of the modern contextual approach. - العظامات خالد فهاد; ابو هولا رياض رزق الله (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study seeks to elucidate the role of context in revealing the opposite connotations in the Noble Qur’an in terms of the so-called vocabulary of opposites, and directing them to the appropriate meaning, unlike their meaning in the lexicons that are common on the tongues among people of language and learners, and perhaps this research called this linguistic phenomenon (reverse sign) ); To be consistent with modern semantics. Here it is necessary to point out the importance of adopting the views of the commentators in guiding the context to what the study tends to discuss and analyze. In order to reach the required significance, noting not to neglect the acceptance of the multiple meanings of the vocabulary of the subject of study by the commentators, as there is no dispute about the existence of semantic multiplicity of one word, and the context remains the decisive factor in determining its precise meaning. Among the order of importance is to note that this study analyzes the linguistic vocabulary in the light of the modern contextual approach. As the aim of the research lies in moving to carefully identify the intended sign.